2015
DOI: 10.1177/1941874415576204
|View full text |Cite
|
Sign up to set email alerts
|

What to do With Wake-Up Stroke

Abstract: Wake-up stroke, defined as the situation where a patient awakens with stroke symptoms that were not present prior to falling asleep, represents roughly 1 in 5 acute ischemic strokes and remains a therapeutic dilemma. Patients with wake-up stroke were excluded from most ischemic stroke treatment trials and are often not eligible for acute reperfusion therapy in clinical practice, leading to poor outcomes. Studies of neuroimaging with standard noncontrast computed tomography (CT), magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 92 publications
(109 reference statements)
1
39
0
Order By: Relevance
“…Patients who were last seen well > 9 h were excluded. This may explain why we found a relatively low time between last seen well and CT for the WUS patients and a relatively low percentage of WUS patients compared to other cohorts [7]. However, the cohort most similar to ours also found similar results [23].…”
Section: Discussionsupporting
confidence: 54%
“…Patients who were last seen well > 9 h were excluded. This may explain why we found a relatively low time between last seen well and CT for the WUS patients and a relatively low percentage of WUS patients compared to other cohorts [7]. However, the cohort most similar to ours also found similar results [23].…”
Section: Discussionsupporting
confidence: 54%
“…After years of time window based recanalization therapies [1][2][3] for patients presenting with acute ischaemic stroke (AIS), the recently published results of the DAWN trial [4] just proved the high value of imaging based selection for treating stroke patients with a late or uncertain time of onset. In fact, the increasing use of advanced imaging has allowed a better understanding of the physiopathological processes occurring during stroke [5][6][7][8]. In 2011, Thomalla et al [9] established that a diffusion weighted imaging/ fluid attenuated inversion recovery (DWI-FLAIR) mismatch could help identify patients within 4.5 h of symptom onset with a positive predictive value of 0.83 and specificity of 0.78, which were even higher when extended to 6 h, respectively 0.95 and 0.85.…”
Section: Introductionmentioning
confidence: 99%
“…36 A few CT-based studies reported similarity in early ischemic changes observed in both WUS and non-WUS. [37][38][39][40] Roveri et al compared early ischemic changes on CT imaging in WUS and non-WUS patients with similar clinical and demographic characteristics. There was a comparable degree of early ischemic change as evidenced by similar amounts of parenchymal hypoattenuation, blurring of the graywhite junction, and swelling as judged by the Alberta Stroke Program Early CT Score (ASPECTS), in the baseline CT scan in both groups.…”
Section: Neuroimaging In Wusmentioning
confidence: 99%